Organisation structure in large public enterprises - "Narain , Laxmi" (Delhi, 1981)
This study aims at providing an account of the organisation structure of five major public enterprises, namely, the Fertilizer Corporation of India, the Indian Oil Corporation, the Bharat Heavy Electricals, the Hindustan Aeronautics and the Hindustan Steel. Each of these companies employs over 15,000 persons, has a capital investment of over Rs. 140 crores, and has four to eleven units, widely spread out in the country.It is hoped that this study would throw some light n this area and lead to deeper and more valuable analyses in this field.
Keywords: Govt. business enterprises